Suddenly - Allen, Lewis, 1905-2000; Sinatra, Frank, 1915-1998; Sale, Richard, 1911-1993.; Libra Productions; Cinetel Films ([Hollywood, CA] : Libra Productions, Inc., 1954)
Three hired gunmen set themselves up to assassinate the President in Suddenly, a California town, where he is secretly scheduled to transfer from a special train to a car. They seize a strategic location in a private residence, and proceed to terrorize the occupants.
Based on the short story Active duty by Richard Sale.
Frank Sinatra, Sterling Hayden, James Gleason, Nancy Gates.
Cinematographer, Charles G. Clarke; editor, John F. Schreyer; music, .
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Assassins -- Drama; Presidents -- Assassination -- United States -- Drama; Hostages -- Drama; Murder for hire -- California -- Drama; United States. -- Secret Service -- Drama; Television -- Receivers and reception -- Drama; Toy guns -- Drama; Korean War, 1950-1953 -- Drama; Thrillers (Motion pictures); Film noir; Feature films; Internet videos; Streaming video